2015
DOI: 10.1002/dneu.22289
|View full text |Cite
|
Sign up to set email alerts
|

Prox1 identifies proliferating neuroblasts and nascent neurons during neurogenesis in sympathetic ganglia

Abstract: Neurogenesis in embryonic sympathetic ganglia involves neuroblasts that resume proliferation following neuronal differentiation. As cell cycle exit is not associated with neuronal differentiation, the identity of proliferating neuroblasts is incompletely understood. Here, we use sympathetic ganglia of chick embryos to define the timing of neurogenesis and neuroblast identity focusing on the expression and function of the transcription factor Prox1. We show that a large fraction of neuroblasts has initially wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 74 publications
(131 reference statements)
0
15
0
Order By: Relevance
“…S5D). For example, Reln and Prox1 are known for their roles in neuronal migration 46,47 and neurogenesis 48,49 ; we, therefore, speculate that they may mark a peripheral neuronal cell type in cluster 11.…”
Section: This Is Consistent With Two Independent Studies In the Smallmentioning
confidence: 91%
“…S5D). For example, Reln and Prox1 are known for their roles in neuronal migration 46,47 and neurogenesis 48,49 ; we, therefore, speculate that they may mark a peripheral neuronal cell type in cluster 11.…”
Section: This Is Consistent With Two Independent Studies In the Smallmentioning
confidence: 91%
“…This marks a difference to parasympathetic neurogenesis as observed in ciliary ganglia [ 136 ]. A detailed kinetic analysis of cell division and differentiation in postganglionic sympathetic neurons of mice and chick has been obtained by the comparison of incorporation of two labeled nucleotides, BrdU and EdU, into the newly synthesized DNA [ 137 , 138 ]. The studies show a temporary deceleration or complete interruption of cell cycling only to resume proliferation after differentiation to the noradrenergic phenotype.…”
Section: Main Textmentioning
confidence: 99%
“…Recent studies have shown that the same cells also express Prox1 and may also require it for neuroblast proliferation and survival (Holzmann et al . ). It will be interesting to analyze the functional relationship between SoxC proteins and Prox1 in these cells and compare it to CNS neurons.…”
Section: Discussionmentioning
confidence: 97%